Analysis of the Effectiveness of Priority Customer Complaint Services at BNI Emerald Services - Nurnabila, Zahra Akilah; Khumayah, Siti (Indonesian Journal of Advanced Research, 2026)
This study examines the effectiveness of complaint handling for BNI Emerald priority customers at Bank BNI KCU Cirebon, where high service expectations contrast with ongoing issues such as slow resolution, inconsistent service quality, and limited follow-up communication. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving priority customers, relationship managers, and customer service officers. Analysis was guided by service effectiveness indicators (Gibson et al.) and complaint handling criteria (Johnston & Mehra). The findings show that while complaint handling follows established procedures, its effectiveness remains suboptimal, particularly in resolution timeliness, information transparency, and customer satisfaction. Staff competence and accessible complaint channels support service delivery, whereas layered escalation, limited personnel, and inconsistent communication hinder optimal performance.